A METHOD OF ESTIMATION THE PARAMETERS OF THE AQUIFERS BASED ON THE DATA OF TESTING FILTRATION WORKS UNDER CONDITIONS OF HYDRAULIC COUPLING - A. V. Malkov; I. M. Pershin; I. S. Pomelyayko (Известия высших учебных заведений: Геология и разведка)
The paper proposes a technique for determining the hydrodynamic parameters under conditions of the hydraulic coupling of the aquifers. A test modeling has shown that the existing methods of determining the flow parameter (Teys, Jacob, Hantush) give significant errors. They can be used only under the assumptions that are made in the derivation of the known calculated dependencies. The accuracy of the determining the overflow parameter has been shown to be largely determined by the ratio of the water loss of the aquifer under study and the adjacent one, which is a source of additional nutrition. For a whole range of tasks, such as income of the poor-quality polluted waters from the donor horizon or studying the dynamics of the mineral water conditioning composition, the processes of overflow can be a determining factor. The proposed technique is free from these shortcomings, but requires a cycle of cluster testing filtration work on all interacting aquifers.